A new era for Italian Journal of Pediatrics - Bernasconi Sergio (BMC, 2008)
Abstract On behalf of the Editorial Board, welcome to the new Italian Journal of Pediatrics, the official journal of the ISP/SIP (Italian Society of Pediatrics/Società Italiana di Pediatria), now publishing on BioMed Central's open access publishing platform. The move to BioMed Central will benefit authors by having their manuscripts published faster with rapid global dissemination. Readers will also benefit from free online access to the journal via the website and a range of full text archives.